Awareness of HIV/AIDS in Pregnant Women (Journal of Fatima Jinnah Medical University, 2018)
Introduction: The human immunodeficiency virus/Acquired immunodeficiency syndrome (HIV/AIDS) pandemic continues its deadly assault in different parts of the world. Over 20 million people have died since the first case of AIDS was identified in 1981.Objectives: Aim of this study was to determine the increase in percentage of cases having correct response regarding knowledge of HIV/AIDS after counseling session. It was conducted in Services Hospital Lahore (SIMS), Gynaecology Unit 2, antenatal clinic in 6 months of period.Results: Most of the patients between 26-30 years i.e. 38%(n=114), mean, frequency of pre-counseling knowledge of HIV/AIDS was in 22.33% (n=67) and after counseling session knowledge of HIV/AIDS was again evaluated which was recorded in 88%(n=264) while frequency of increase percentage of cases having correct response regarding HIV/AIDS after counseling was recorded 62.33% (n=197) by subtracting 88%(n=264) after counseling session from 22.33%(n=67) pre-counseling knowledge.Conclusion: It was concluded that after counseling session regarding knowledge of HIV/AIDS, a significant increase in percentage of cases having correct response is achieved and this type of counseling at antenatal clinic is useful for the protection from morbidity.
Keywords: HIV/AIDS, knowledge, counseling session, correct response